Viabilidade de urediniósporos de Phakopsora euvitis ono e controle da ferrugem da videira com fosfito - Scapin, Cláudia Regina (2009)
Grapevine rust (Phakopsora euvitis) causes early defoliation of grape plants, damaging fruit ripening and branch development. Even though it is a macrocyclic rust in Asia, only the telial and uredinial stages have been observed in Brazil. Then, rusted grapevine leaves are presumed to be the only source of urediniospores for grapevine rust epidemics in the country. Aiming to get more information about epidemiology and control of this disease in Brazil, this study had the following objectives: (i) (i) to analyze the viability of P. euvitis urediniospores collected from uredia from the beginning of sporulation until the death of grape leaves; (ii) to analyze the effect of temperature on viability of P. euvitis urediniospores removed from leaves during preservation time; and (iii) to evaluate the protective, curative and erradicant effects of potassium phosphyte on grapevine rust control under growth chamber conditions. The assays were carried out with "Niagara" grape (Vitis vinifera x Vitis labrusca) plants growth in pots, having at least 5-6 fully developed leaves, which were inoculated with standard urediniospore suspension. The percentage of germination of urediniospores was evaluated in water-agar medium 2% and the infection efficiency was assessed on grape leaves. It was estimated that urediniospores remained infective for until 133 days since the beginning of sporulation on leaves of plants that were kept in growth chamber, under controlled temperature and light conditions, without leaf wetness. However, under field conditions, the estimated infectivity of urediniospores was only 54 days on leaves kept attached to the plant until leaf drop. On leaves removed from plants at 10 days after inoculation and kept in the soil surface, the urediniospores remained infective for only 21 days. Additionally, it was found that urediniospores which were collected three days after the latent period and kept in Eppendorf tubes, without adding additives, showed 90% of reduction on infection efficiency during the 120-day storage period at the temperatures of -20ºC (freezer) and 25±2ºC (growth chamber). All treatments that were evaluated for breaking spore dormancy did small improvement of spore germination and infection efficiency. The assay with protective fungicides, carried out in growth chamber, with sprayings at 2, 5 or 8 days before rust inoculation, showed that potassium phosphyte was less efficient (25 to 64% control) compared with copper hydroxide (99% control) and tebuconazole (100% control), causing also reduction on urediniospore germination. The curative or erradicant fungicide trial, with sprayings at 2, 5 or 8 days before rust inoculation, showed that potassium phosphyte was less efficient (25 to 58% control) compared to copper hydroxide (40 to 60% control) and tebuconazole (100% control). Also, Potassium phosphyte and copper hydroxide treatments caused significant reduction on urediniospore viability, and the tebuconazole treatment stopped sporulation even by spraying at 8 days after inoculation.